Mutation analysis of 19 commonly used short tandem repeat loci in a Guangdong Han population. (May 2018) - Xiao, Cheng; Peng, Zhiyong; Chen, Feilong; Yan, Hui; Zhu, Bofeng; Tai, Yunchun; Qiu, Pingming; Liu, Chao; Song, Xuheng; Wu, Zihao; Chen, Ling
Highlights: Mutation rates and mutation characteristics of 19 loci from 9, 626 cases in a Guangdong Han population were investigated. The mutation data was compared with eight other populations and the differences were identified. The relationship between mutation rate and heterozygosity, allele size, parental age was studied. Abstract: Short tandem repeats (STRs) are the most widely used genetic markers in current forensic practice. However, STR mutations have troubled paternity test all the time. To ensure the accuracy in parentage testing, it is important to obtain population mutation data and identify factors that affect STR mutation rates. In the present study, we performed a comprehensive analysis on 322 mutation events in 19 autosomal STR loci from 12, 752 meiotic events in 9, 626 parentage test cases. The average mutation rate for the 19 STR loci was estimated at 1.329‰ per meiosis. Most mutations were single-step and occurred in the male germline. Further, the mutation rates increased with the paternal age at child birth, but not the maternal age. Multidimensional scaling analysis showed differences in the profiles of the mutation rates of the 13 CODIS STR loci among several different worldwide populations. Our findings also showed that locus-specific mutation rates were correlated with heterozygosity, and longer alleles have higher mutation rates than shorter alleles do. The data from our study may provide useful information for parentage testing, kinship analysis, and population genetics.